2006
DOI: 10.1537/ase.040710
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary investigations of the Chelechol ra Orrak Cemetery, Republic of Palau: I, skeletal biology and paleopathology

Abstract: The Pacific Islands were the last major geographic region settled by humans. The physical remains of these settlers, who probably arrived within the last 4500 years, are rare. At the Chelechol ra Orrak site in the Palau archipelago of Micronesia, the discovery of a cemetery dating to near 3000 BP presents an opportunity to examine what portends to be a large sample of the earliest peoples to inhabit the western Pacific. This report is intended as an introduction to the human skeletal remains recovered to date … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 24 publications
0
35
0
Order By: Relevance
“…The unexpected discovery of human burials dating back to ca. 3000 BP (Fitzpatrick, 2003a;Fitzpatrick and Nelson, 2008;Nelson and Fitzpatrick, 2006) demonstrates that Chelechol ra Orrak was initially used as a cemetery, similar to other caves and rockshelters scattered through the Rock Islands during this time period (Fitzpatrick and Nelson, 2008). Continued research in 2002 and 2007 indicated that the site also had subsequent phases of prehistoric occupation up to the historic period (Fitzpatrick and Kataoka, 2005).…”
Section: The Chelechol Ra Orrak Sitementioning
confidence: 93%
“…The unexpected discovery of human burials dating back to ca. 3000 BP (Fitzpatrick, 2003a;Fitzpatrick and Nelson, 2008;Nelson and Fitzpatrick, 2006) demonstrates that Chelechol ra Orrak was initially used as a cemetery, similar to other caves and rockshelters scattered through the Rock Islands during this time period (Fitzpatrick and Nelson, 2008). Continued research in 2002 and 2007 indicated that the site also had subsequent phases of prehistoric occupation up to the historic period (Fitzpatrick and Kataoka, 2005).…”
Section: The Chelechol Ra Orrak Sitementioning
confidence: 93%
“…Archaeological investigation at the site began in 2000 (Test Units 1-4) with additional fieldwork in 2002 and 2007 (Test Units e2/S1, e3/S1, e2/S2, e1/S4, and e1/S5, shown in white on Figure 2). research has primarily revolved around the analysis of early human burials (Fitzpatrick 2003a;nelson and Fitzpatrick 2006;), but also includes examination of later periods of prehistoric occupation (Fitzpatrick and Kataoka 2005) and use of the site by yapese islanders for quarrying stone money (Fitzpatrick 2003b(Fitzpatrick , 2008. Although analysis of the archaeological assemblage is ongoing, it has already revealed a rich collection of human burials, shell, stone and bone artefacts, ceramics, and faunal remains, particularly mollusks and fish.…”
Section: Archaeological Backgroundmentioning
confidence: 99%
“…Statistical tests further confirm the remarkable homogeneity of size in prehistoric Palauans. Upper and lower limb elements from Chelechol ra Orrak are not consistently larger than corresponding specimens from the Rock Island sites [7], [8]. An associated femur and tibia from Chelechol ra Orrak are within the size range of small-bodied humans.…”
Section: Discussionmentioning
confidence: 75%